2016
DOI: 10.3803/enm.2016.31.4.577
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent Rate of Nonalbuminuric Renal Insufficiency and Its Association with Cardiovascular Disease Event in Korean Type 2 Diabetes

Abstract: BackgroundNonalbuminuric renal insufficiency is a unique category of diabetic kidney diseases. The objectives of the study were to evaluate prevalent rate of nonalbuminuric renal insufficiency and to investigate its relationship with previous cardiovascular disease (CVD) event in Korean patients with type 2 diabetes mellitus (T2DM).MethodsLaboratory and clinical data of 1,067 subjects with T2DM were obtained and reviewed. Study subjects were allocated into four subgroups according to the CKD classification. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…This proportion seemed quite low compared with the 39% reported in this paper [9]. This discrepancy might indicate that the subjects of this retrospective study did not represent the patients observed in the real clinical settings.…”
contrasting
confidence: 73%
See 2 more Smart Citations
“…This proportion seemed quite low compared with the 39% reported in this paper [9]. This discrepancy might indicate that the subjects of this retrospective study did not represent the patients observed in the real clinical settings.…”
contrasting
confidence: 73%
“…In this issue of Endocrinology and Metabolism , Lee et al [9] reported that nonalbuminuric stage ≥3 CKD group (<60 mL/min/1.73 m 2 ) was a significant category of diabetic nephropathy, and that the patients belonging to this category showed higher prevalence of CVD and retinopathy than those with preserved eGFR (≥60 mL/min/1.73 m 2 ). Because this group had shorter diabetic duration than the albuminuric stage ≥3 CKD group, nonalbuminuric stage probably proceed to albuminuric stage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In detail, prevalence was: 40.1% in the Developing Education on Microalbuminuria for Awareness of renal and cardiovascular risk in Diabetes (DEMAND) Study (multinational, MDRD, 2003) [27,28]; 51.8% in the Japan Diabetes Clinical Data Management (JDDM) Study (Japan, MDRD, 2004e2005) [29]; 54.2% in the National Evaluation of the Frequency of Renal Impairment cO-existing with NIDDM (NEFRON) (Australia, MDRD, 2005) [30,31] [38]. Lower prevalence rates were reported in two epidemiological surveys from Korea (23.7%) [39] and US (the Chronic Renal Insufficiency Cohort [CRIC] Study, 28.4%) [40], but patients whose albuminuria status was possibly related to RAS blocker therapy were excluded from these analyses.…”
Section: Nonalbuminuric Renal Impairment and Progressive Renal Declinementioning
confidence: 99%
“…Bae [27] reviewed the cardiovascular safety of diabetic drugs, and Kang and Jung [30] reviewed the cardiovascular effects of glucagon-like peptide-1 receptor agonists. Many articles on the topic of diabetes and obesity were published in the remaining issues of 2016 [313233343536373839404142]. …”
Section: Articles On Diabetes Obesity and Lipid Disordersmentioning
confidence: 99%